Dekonstruksi Stigma Radikalisme: Analisis Filosofis Tentang Hubungan Agama dan Negara Dalam Upacara 17 Agustus 2022 di Pondok Ngruki - Zahrodin Fanani; Kafin Jaladri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This research analyzes the deconstruction of radicalism stigma through the perspective of Islamic philosophy in the context of the relationship between religion and state, with a case study of the August 17, 2022 ceremony at Pondok Ngruki. The event, attended by Minister Muhadjir, became a symbolic moment in changing the dominant narrative about radicalism often associated with this pesantren. The research uses a qualitative approach with philosophical analysis, examining the concept of harmony between Islamic values and nationalism, as well as the application of Derrida's deconstruction theory in recontextualizing pesantren practices. The research results show that this ceremony reflects the integration of Islamic values with nationalism, proving the role of Islamic education in building national character while simultaneously reducing the stigma of radicalism. By prioritizing harmony between religion and the state, Pondok Ngruki demonstrates the relevance of Islamic teachings in supporting the principles of nationalism. This study recommends further research in other pesantren to understand similar patterns and strengthen collaboration between pesantren and the government in promoting national values.